Faktor-Faktor yang Berhubungan dengan Persalinan Persalinan Kala II Memanjang di Puskesmas Banjit Lampung - Eka Febri Yanti Asri; Maryati Sutarno (Universitas Malahayati, 2025)
ABSTRACT The large impact caused by the long second stage of labor can even cause death of the fetus. The prevalence of women giving birth with a long second stage of labor in 2020 at the Banjit Lampung health center was 21 cases (3.5%), in 2021 there were 20 cases (3.2%) and in 2023 there were 34 cases (4.3%). Objective: to study the factors associated with prolonged second stage events at the Banjit Lampung Community Health Center in 2024. Analytical survey, with a cross sectional approach, the population in this study were all mothers giving birth at the Banjit Lampung Community Health Center from January to September 2024 as many as 166 people, with a random sampling technique with a sample size of 63 respondents, using data namely secondary data with a checklist sheet, univariate and bivariate analysis using chi square. From the results of univariate statistical tests of 63 respondents, 21 mothers From the results of the Chi Square test, there is an age relationship (ρ value = 0.002, OR value = 7.045) , fetal size (ρ value = 0.000), Premature rupture of membranes (ρ value = 0.002, OR value = 7.045) with prolonged second stage incidence at the Banjit Lampung Community Health Center in 2024, with. There is no relationship between parity (ρ value = 0.317) with the incidence of stage II of Elongation at the Banjit Lampung Community Health Center in 2024. There is a relationship between age and fetal weight with the incidence of premature rupture of membranes in mothers giving birth, so this research can be used as a reference in providing emergency services during labor following PMK No. 21 of 2021. Keywords: Fetal Size, Long Second Stage, Premature Rupture of Membranes, Parity, Age ABSTRAK Besarnya dampak yang ditimbulkan akibat persalinan Kala II Memanjang, bahkan dapat menyebabkan kematian pada janin. Prevalansi ibu bersalin dengan persalinan Kala II Memanjang pada tahun 2020 di puskesmas Banjit Lampung sebanyak 21 kasus (3.5%), pada tahun 2021 sebanyak 20 kasus (3.2%) dan pada tahun 2023 sebanyak 34 kasus (4.3%). Untuk mempelajari Faktor-Faktor yang Berhubungan dengan Persalinan kala II memanjang di Lampung Tahun 2024. Survei Analitik, dengan pendekatan secara cross sectional, populasi dalam penelitian ini seluruh ibu bersalin di Puskesmas Puskesmas Banjit Lampung dari bulan Januari s/d September 2024 sebanyak 166 orang, dengan teknik random samplling dengan jumlah sample 63 responden, memakai data yaitu data sekunder dengan lembar cheklist, analisis univariat dan bivariat menggunakan chi square. Dari hasil uji uji Chi Square yaitu Ada hubungan usia (nilai ρ value = 0,002, nilai OR=7.045), besar janin (ρ value = 0,000), Ketuban pecah Dini (ρ value = 0,002, nilai OR=7.045)dengan persalinan kala II memanjang di Puskesmas Banjit Lampung Tahun 2024. Tidak ada hubungan paritas (ρ value = 0,317) dengan persalinan kala II memanjang di Puskesmas Banjit Lampung Tahun 2024. Adanya hubungan umur, berat janin dengan kejadian ketuban pecah dini pada ibu bersalin, sehingga dengan adanya penelitian ini dapat dijadikan acuan dalam memberikan layanan kegawatdaruratan pada masa persalinan sesai PMK No 21. Tahun 2021. Kata Kunci: Besar janin, Kala II Memanjang, Ketuban pecah Dini, Paritas, Umur